(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the scientific legacy of the great encyclopedic scholar and medieval Eastern thinker Abu Ali Ibn Sina, particularly his invaluable works in the field of medicine. The study highlights the scientific and philosophical significance of his work The Canon of Medicine and the medical concepts presented in it. Special attention is given to Ibn Sina’s poetic treatises, where issues of preserving human health, the causes of diseases, as well as their prevention and treatment methods are analyzed in detail. The article also provides a scholarly evaluation of the thinker’s views on the interrelation between the human body, lifestyle, and the natural environment-ideas that remain relevant for modern medicine. Furthermore, the role of Ibn Sina’s heritage in contemporary healthcare, especially in preventive medicine, the promotion of a healthy lifestyle, and the study of psychological factors influencing illnesses, is thoroughly discussed.